PENGELOLAAN AKTIVITAS WISATAWAN OLEH KANTOR UNIT TAMAN WISATA CANDI PRAMBANAN DI KABUPATEN KLATEN, JAWA TENGAH - Olivia Azarine Purinka; Andri Sulistyani (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2023)
ABSTRACT Something for tourists to see, activities that can be carried out by tourists, and something that can be purchased by tourists are the concepts of tourism activities that must be owned by tourist destinations. In the Prambanan temple area, the three main concepts have entered and made the Prambanan temple area a tourist destination. With an area of up to eighty hectares, the Prambanan temple area must be managed so that tourists don't get confused while in the temple area. In addition to managing the temple, the Prambanan unit manager is in charge of managing tourists to ensure that everything runs smoothly and efficiently. By using a qualitative method with a descriptive approach, the authors try to describe the actual conditions by collecting information in the field and explaining it in descriptive form without testing hypotheses or making predictions in this study. This research explains how the Prambanan unit office manages tourist activities. The purpose of this study is to explain how the Prambanan unit office conducts tourism activities. According to the results of the study, tourist activity management occurs by managing the master plan as well as garden layout and plant care, arranging ride tickets for tourists, overseeing and guarding the socialization of visit regulations to setup traders, and so on. It may be determined that the Prambanan unit office's management of tourist activities has been completed and is functioning properly. Keywords: Management, Tourist Activity, Unit Office of the Prambanan Temple